GAMBARAN KARAKTERISTIK DAN KECEMASAN IBU HAMIL TRIMESTER I TERHADAP PEMERIKSAAN TRIPLE ELIMINASI - Putri Maretyara Saptyani; Resti Ikhda Syamsiah; Laeli Farkhah Farkhah (Masker Medika, 2024)
Introduction: Triple Elimination is a health program based on the legal foundation of the Minister of Health Regulation number 52 of 2017 concerning the "Elimination of the transmission of Human Immunodeficiency Virus, Syphilis, and Hepatitis B from mother to child." Data obtained from the Cilacap District Health Office in 2023 shows that the coverage of triple elimination screenings for pregnant women in Cilacap District in 2023 has not yet reached the National target, with HIV screening coverage at 59.81%, Hepatitis B screening at 61.85%, and Syphilis screening at 59.71%. Method: This study is a type of descriptive analytic research. At this stage, the research design used is the quantitative method. The research was conducted in a single phase from August to September 2024. Results: there were pregnant women who experienced mild anxiety towards the triple elimination test, totaling 53 people, and moderate anxiety, totaling 2 people. Discussion: Pregnant women with mild anxiety are mostly from non-risk age groups, educated at the junior high to senior high school level, receive family support, and belong to the primigravida group. Pregnant women with moderate anxiety are mostly from risk age groups, educated at the elementary school level, receive family support, and belong to the primigravida group. Keywords: anxiety, triple elimination, pregnant women